Early Warning Model and Currency Crisis in the Iranian Economy A Probit Approach - Mohammadjavad Khosrosereshki; Yavar Dashtbany (پژوهشهای اقتصادی)
Aim and Introduction In managed floating exchange rate systems, one of the important issues facing monetary policymakers is defining the exchange rate corridor and committing to it. In developing countries (with a low flow of foreign capital and limited access to international financial markets), it is difficult to follow committed policies. Iran is not only an oil-exporting country but also has limited access to export earnings due to sanctions. The central bank is heavily dependent on the government policies. Consequently, these causes have led to 5 currency crises since 1991. Therefore, having an early warning system for Iran’s exchange market is essential for monetary policymakers. One of the prominent aspects of this study is the definition of crisis index, which considers not only the direct intervention of the central bank in the exchange market but also both the exchange rate growth and the central bank’s foreign reserve growth rate. Finally, using the Probit approach, an early warning system with a low noise-to-signal ratio is proposed. Methodology Quarterly data from 1990 to 2023 for Iran and the United States were used in the model. Domestic data represent the real and monetary sectors of Iran’s economy, and U.S. data represent the world economy. First, using Bai-Perron (1997) and oil revenue as a state variable of the economy, the duration was divided into three periods: low oil revenue, high oil revenue, and sanctions. The random walk equation was estimated. logoil t =a+b  logoil t-1 + ε t                                                                (1) Second, for each period, according to Weymark's (1995) model, the exchange market pressure (EMP) and direct intervention indices were calculated. Then the average and standard deviation of both the exchange rate growth and the central bank’s foreign reserve growth rate were calculated. Third, the situation in each quarter is determined as shown in Tables 1 and 2: Table 1: The situation in each quarter in leaning with the wall intervention type